2008
DOI: 10.3171/spi/2008/8/3/230
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anatomical variations of bone and vascular structures around the posterior atlantal arch using three-dimensional computed tomography angiography

Abstract: Object The current study evaluates the incidence of anatomical variations of the V3 segment of the vertebral artery (VA) and the posterior arch of the atlas (C-1). Failure to appreciate these types of anatomical variations can cause catastrophic injury to the VA during posterior approaches to the upper cervical spine. Methods In the present study, the authors analyzed the records of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 20 publications
3
103
2
Order By: Relevance
“…10,13,15,17,20,23 On radiographic studies, the bridge was found in 11-15.6%. 4,11,20,24 The incidence of osseous bridges in our study was lower than those in past reports, and it is difficult to explain the cause of this wide disparity. This difference might result from the different modalities of investigation used, which have included cadaveric study, plain radiography study, and 3D CT study.…”
Section: Anatomical Variations and Anomaliescontrasting
confidence: 54%
See 1 more Smart Citation
“…10,13,15,17,20,23 On radiographic studies, the bridge was found in 11-15.6%. 4,11,20,24 The incidence of osseous bridges in our study was lower than those in past reports, and it is difficult to explain the cause of this wide disparity. This difference might result from the different modalities of investigation used, which have included cadaveric study, plain radiography study, and 3D CT study.…”
Section: Anatomical Variations and Anomaliescontrasting
confidence: 54%
“…The incidence of the osseous bridge may also vary among races across the world. 11,15 If the formation of the bridge relates to the aging process as osteophyte formation does, the incidence would vary depending on the patient population or the material used in each study. In the present investigation, when the extent of coverage was long enough to hide the VA or the VA itself was short, the VA showed little or no protrusion.…”
Section: Anatomical Variations and Anomaliesmentioning
confidence: 99%
“…When making the decision as to which method is most appropriate, surgeons need to consider several individual patient factors, as follows. First, some types of vertebral artery anomalies such as a persistent first intersegmental artery and fenestrated vertebral artery may preclude the use of C1 lateral mass screws [27], which is usually used in conjunction with C2 pedicle screws. In Fig.…”
Section: Interpretation Of Study Resultsmentioning
confidence: 99%
“…9,10) The sagittal angle of the C0-C1 transarticular screw at the junctional entry point is significantly steeper than that at the caudal C1 arch point. Therefore, the caudal C1 arch point may be more convenient for screw insertion and screw head alignment with the other screws.…”
Section: Discussionmentioning
confidence: 99%